2017
DOI: 10.4172/2476-2059.1000120
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge about Food Spoilage and Principles of Food Preservation among Saudi Women in Jeddah

Abstract: Food spoilage can be defined as any sensory change of the food which becomes harmful to consumers and unsuitable to eat. Therefore, the purpose of this study was to discover the degree of awareness and understanding about food spoilage and preservation among Saudi women in Jeddah. Questionnaires were developed and distributed among female students (n=110) in King Abdul-Aziz University. The data were used to conduct frequency analysis. The results demonstrated that 84.6% (1.8 ± 1.0) of respondents agreed that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
2
4
1
Order By: Relevance
“…Remarkably, 63.3% of male participants demonstrated a satisfactory level of PRKHB in this study. This result indicates a disparity with former studies, where the females displayed a high level of familiarity with and adherence to food safety compared to the males ( Da Costa et al, 2016 ; Ruby et al, 2019 ; Shori, 2017 ). Traditionally females were the primary food preparers in the household and those with the most food safety concern.…”
Section: Discussioncontrasting
confidence: 90%
“…Remarkably, 63.3% of male participants demonstrated a satisfactory level of PRKHB in this study. This result indicates a disparity with former studies, where the females displayed a high level of familiarity with and adherence to food safety compared to the males ( Da Costa et al, 2016 ; Ruby et al, 2019 ; Shori, 2017 ). Traditionally females were the primary food preparers in the household and those with the most food safety concern.…”
Section: Discussioncontrasting
confidence: 90%
“…As in earlier studies [8,[70][71][72][73][74], it was found that it was women (clusters D, C, and B) who demonstrated better food safety knowledge and practices than men (clusters E and A). On the basis of the characteristics of the identified clusters, it can be seen that this is one of the key factors determining the correctness of the answers given.…”
Section: Discussionsupporting
confidence: 64%
“…Each kind of foods has its natural characteristics such as appearance, texture, smell, taste and flavor. Therefore, any change in one or more of these characteristics of food indicates the food spoilage which may cause illness because of the presence of pathogenic microorganisms and their toxins [3]. After the death of fish, spoilage bacteria enter the muscle from the skin and gills, disintegrate the muscle cells and take necessary energy to grow.…”
Section: Introductionmentioning
confidence: 99%